Pendampingan Peningkatan Brand Image Produk UMKM Takoyaki di Sidoarjo - Imamatuz Zakiyah; Farichatul Khafidah; Laily Muzdalifah (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: MSME Mr. Takoyaki is to encourage business actors to reveal their potential so that they are able to create and develop their business which is located at Jalan Kemantren Tulangan Sidoarjo. Methodology: This research uses qualitative methods, which focus more on conducting in-depth understanding by examining problems specifically The MSMEs that we assist are MSME Result: Mr. Takoyaki which is located at Jalan Kemantren Reinforcement, Sidoarjo. The results of Mr. Takoyaki's MSME assistance are improvements to product packaging, product labels, payment systems, and marketing. Efforts to develop MSMEs in Indonesia are one aspect that is of concern to the government in economic development. MSME mentoring by students is one of the community service activities, based on a survey conducted there are several problems that must be developed so that MSMEs can develop gradually, therefore MSME owners need to be equipped with knowledge and socialization about good digital marketing service activities. community service is part of the Tri Dharma of Higher Education, therefore it must be carried out both for each student and for the Implementation Team to carry out this service consisting of Management students at the Faculty of Economics, Nahdatul Ulama University. Conclusions: The goals to be achieved in this activity are: Improving MSMEs Mr. Takoyaki Mr.s. Eni Rahmawati so that the payment system for Mr. Takoyaki is more updated, determining Google Maps so that consumers can find out where Mr. Takoyaki is, and is better known by consumers with a wider range.